2016
DOI: 10.1161/circimaging.115.003597
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Echocardiographic Measures in a Hispanic/Latino Population With the 2005 and 2015 American Society of Echocardiography Reference Limits (The Echocardiographic Study of Latinos)

Abstract: Background Reference limits for echocardiographic quantification of cardiac chambers in Hispanics are not well studied. Methods and Results We examined the reference values of left atrium (LA) and ventricle (LV) structure in a large ethnically diverse Hispanic cohort. Two-dimensional transthoracic echocardiography was performed in 1,818 participants of the Echocardiographic Study of Latinos (ECHO-SOL). Individuals with body mass index ≥30kg/m2, hypertension, diabetes mellitus, coronary artery disease and atr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 20 publications
4
14
0
2
Order By: Relevance
“…The present study by Qureshi et al 10 adds to the body of literature supporting the importance of ethnicity, for whatever reasons, to cardiac structural adaptations in health and disease. Whether this represents nature, nurture, or combination of the 2 will require much additional research to determine.…”
Section: Gottdienersupporting
confidence: 57%
“…The present study by Qureshi et al 10 adds to the body of literature supporting the importance of ethnicity, for whatever reasons, to cardiac structural adaptations in health and disease. Whether this represents nature, nurture, or combination of the 2 will require much additional research to determine.…”
Section: Gottdienersupporting
confidence: 57%
“…Racial and ethnic differences in LV mass, diastolic function, systolic function and myocardial deformation are not completely explained by cardiometabolic risk factors and comorbidities 35. Within Echo-SOL, the average values of LV size and mass are different than what has been reported in non-Hispanic white cohorts of healthy participants 36. Additionally, LV diastolic dysfunction is more highly prevalent in Hispanics/Latinos than in cohorts of non-Hispanic whites 37.…”
Section: Discussionmentioning
confidence: 95%
“…It has been demonstrated that ethnicity and genetic factors contribute to explain the variability in LA dimensions. A recent systematic review based on 36 studies (only one with data from South America) including 30 607 children and adolescents underlined the importance of using race‐specific reference ranges for left cardiac chamber dimensions, as well as the need for standardizing echocardiographic methods in deriving the reference ranges .…”
Section: Discussionmentioning
confidence: 99%
“…However, data from South American populations are scarce and unfortunately; in general terms, subjects from South America have been particularly underrepresented when evaluating cardiac (ie, LA) structure and function to define reference values. 10,16,17 The above is true not only for adults, but also when considering children and adolescents. Furthermore, to our knowledge, the expected (reference) levels for structural and functional LA parameters in children and adolescents from South America are to be assessed.…”
Section: Ta B L E 1 (Continued)mentioning
confidence: 99%
See 1 more Smart Citation